Additively manufactured air-cooled lightweight rotor for an automotive electric motor - Bieber, Maximilian; Haase, Michael; Tasche, Frederik; Zibart, Alexander; Ponick, Bernd (2023 IEEE International Electric Machines & Drives Conference (IEMDC))

Future of electric motors: Additive manufacturing of components with innovative lightweight and cooling structures - Magerkohl, Sebastian; Haase, Michael; Magyar, Balázs

AnnoPy. Ein digitales Tool zur Förderung von Textkompetenzen - Rezat, Sara; Scholle, Oliver (Medien im Deutschunterricht)
Im Beitrag wird ein digitales Tool zur fächerübergreifenden Förderung von Textkompetenzen vorgestellt. Zunächst werden die Funktionen des Tools beschrieben und das zugrundeliegende tool-based task Design erläutert. Anhand eines Lehr-Lern-Arrangements zum argumentierenden Schreiben wird exemplarisch gezeigt, wie das Tool im Deutschunterricht eingesetzt werden kann. Anschließend werden erste empirische Befunde aus der am Design-Based-Research orientierten Studie vorgestellt. Abstract (english): AnnoPy – A digital tool for cross-curricular text literacy development In this article we present a digital tool for cross-curricular text literacy development. At first, we describe the basic functions of the tool and the underlying tool-based task design. After that, a teaching arrangement for German lessons is used to show how the tool can be used to foster argumentative writing. Subsequently, first results of the design-based study are presented.
Keywords: Textkompetenz; Digitales Lesen und Schreiben; Kollaborativer Umgang mit Texten; Prozedurenorientierte Schreibdidaktik; Design-based-Research

(K)ein Ende des "Alten Bundes"? Paulinische Schrifthermeneutik in 2 Kor 3, - Taschl-Erber, Andrea (Heilige Texte. Verständigungen zwischen Theologie und Kulturwissenschaft)

Armutssensibilität – eine Leerstelle in der Religionslehrkräftebildung - Uppenkamp, Vera (Katechetische Blätter)

Downwind and upwind approximations for mesh and model adaptivity of elasto‐plastic composites - Tchomgue Simeu, Arnold; Mahnken, Rolf (PAMM)
Abstract The use of heterogeneous materials, such as composites with Prandtl‐Reuss‐type material laws, has increased in industrial praxis, making finite element modeling with homogenization techniques a well‐accepted tool. These methods are particularly advantageous to account for microstructural mechanisms which can be related to nonlinearities and time‐dependency due to elasto‐plasticity behavior. However, their advantages are diminished by increasing computational demand. The present contribution deals with the balance of accuracy and numerical efficiency of nonlinear homogenization associated with a framework of goal‐oriented adaptivity, which takes into account error accumulation over time. To this end, model adaptivity of homogenization methods is coupled to mesh adaptivity on the macro scale. Our new proposed adaptive procedure is driven by a goal‐oriented a posteriori error estimator based on duality techniques using downwind and upwind approximations. Due to nonlinearities and time‐dependency of the plasticity, the estimation of error transport and error generation is obtained with a backward‐in‐time dual method despite a high demand on memory capacity. In this contribution, the dual problem is solved with a forward‐in‐time dual method that allows estimating the full error during the resolution of the primal problem without the need for extra memory capacity. Finally, a numerical example illustrates the effectiveness of the proposed adaptive approach.
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics

Towards Green Driving - Income Taxes Incentives for Plug-In Hybrids - Giese, Henning; Holtmann, Svea

Riegel, Ulrich / Zimmermann, Mirjam (2022). Evaluation des konfessionell-kooperativen Religionsunterrichts in Nordrhein-Westfalen. Stuttgart: Kohlhammer. ISBN 978-3-17-043134-8. 333 Seiten. - Hüster, Jonas Maximilian (Religionspädagogische Beiträge)
Keywords: Religious studies; Education

Schreibfokussierte Graduiertenförderung: Reflexive Spezialisierung für interdisziplinäre Forschungskontexte - Scharlau, Ingrid; Karsten, Andrea (Neues Handbuch Hochschullehre)

What is AI Ethics? Ethics as means of self-regulation and the need for critical reflection - Alpsancar, Suzana (International Conference on Computer Ethics 2023)

Defense-in-Depth als neues Paradigma der sicherheitsgerechten Produktentwicklung: interdisziplinäre, bedrohungsbewusste und lösungsorientierte Security - Gräßler, Iris; Bodden, Eric; Wiechel, Dominik; Pottebaum, Jens (Konstruktion)
inhalt Der verlässliche Betrieb von technischen Produkten wird zunehmend durch bewusste Angriffe bedroht. Vollständige Sicherheit ist dabei nicht möglich, durchschlagende Angriffe sind unvermeidbar (Assume Breach). Dies erfordert einen Paradigmenwechsel in der sicherheitsgerechten Entwicklung mechatronischer und cyber-physischer Systeme hin zu Defense-in-Depth. Systeme müssen so ausgelegt werden, dass sie auch bei gezielten Angriffen möglichst hohe Zuverlässigkeit und Sicherheit gewährleisten. Der hier beschriebene Lösungsansatz erweitert das Systemmodell um Angriffsszenarien und Verteidigungslinien. Diese werden am Beispiel eines industriellen Schließsystems zur Anlagensicherheit erläutert. Entwickler werden sensibilisiert, Angriffe systematisch zu berücksichtigen und interdisziplinär Verteidigungselemente gegenüber Bedrohungen und Angriffen zu spezifizieren.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science; Theoretical Computer Science

Impulse 6. Texte und Bilder zur Kunstvermittlung: ABHÄNGEN. Ein interdisziplinäres Projekt zur documenta fifteen (2022).

Schreiben als Wissensproduktion? Eine Mikroanalyse der Vielstimmigkeit akademischer Selbstbildung und Enkulturation - Karsten, Andrea (Bedingungen der Wissensproduktion. Qualifizierung, Selbstoptimierung und Prekarisierung in Wissenschaft und Hochschule)

Wie hängen Schreiben und Identität zusammen? Schreibberatung als Raum für die Thematisierung und Entwicklung eines 'Dialogical Self' - Karsten, Andrea (Neue Perspektiven auf Schreibberatung)

On‐Demand Indistinguishable and Entangled Photons Using Tailored Cavity Designs - Bauch, David; Siebert, Dustin; Jöns, Klaus; Förstner, Jens; Schumacher, Stefan (Advanced Quantum Technologies)
Abstract The biexciton‐exciton emission cascade commonly used in quantum‐dot systems to generate polarization entanglement yields photons with intrinsically limited indistinguishability. In the present work, it focuses on the generation of pairs of photons with high degrees of polarization entanglement and simultaneously high indistinguishability. It achieves this goal by selectively reducing the biexciton lifetime with an optical resonator. It demonstrates that a suitably tailored circular Bragg reflector fulfills the requirements of sufficient selective Purcell enhancement of biexciton emission paired with spectrally broad photon extraction and twofold degenerate optical modes. The in‐depth theoretical study combines (i) the optimization of realistic photonic structures solving Maxwell's equations from which model parameters are extracted as input for (ii) microscopic simulations of quantum‐dot cavity excitation dynamics with full access to photon properties. It reports non‐trivial dependencies on system parameters and use the predictive power of the combined theoretical approach to determine the optimal range of Purcell enhancement that maximizes indistinguishability and entanglement to near unity values, here specifically for the telecom C‐band at 1550 nm.
Keywords: tet_topic_qd

On-demand indistinguishable and entangled photons at telecom frequencies using tailored cavity designs - Bauch, David; Siebert, Dustin; Jöns, Klaus; Förstner, Jens; Schumacher, Stefan
The biexciton-exciton emission cascade commonly used in quantum-dot systems to generate polarization entanglement yields photons with intrinsically limited indistinguishability. In the present work we focus on the generation of pairs of photons with high degrees of polarization entanglement and simultaneously high indistinguishibility. We achieve this goal by selectively reducing the biexciton lifetime with an optical resonator. We demonstrate that a suitably tailored circular Bragg reflector fulfills the requirements of sufficient selective Purcell enhancement of biexciton emission paired with spectrally broad photon extraction and two-fold degenerate optical modes. Our in-depth theoretical study combines (i) the optimization of realistic photonic structures solving Maxwell's equations from which model parameters are extracted as input for (ii) microscopic simulations of quantum-dot cavity excitation dynamics with full access to photon properties. We report non-trivial dependencies on system parameters and use the predictive power of our combined theoretical approach to determine the optimal range of Purcell enhancement that maximizes indistinguishability and entanglement to near unity values in the telecom C-band at $1550\,nm$.
Keywords: tet_topic_phc; tet_topic_qd

Softsensors: key component of property control in forming technology - Homberg, Werner; Arian, Bahman; Arne, Viktor; Borgert, Thomas; Brosius, Alexander; Groche, Peter; Hartmann, Christoph; Kersting, Lukas; Laue, Robert; Martschin, Juri; Meurer, Thomas; Spies, Daniel; et al. (Production Engineering)
Abstract The constantly increasing challenges of production technology for the economic and resource-saving production of metallic workpieces require, among other things, the optimisation of existing processes. Forming technology, which is confronted with new challenges regarding the quality of the workpieces, must also organise the individual processes more efficiently and at the same time more reliably in order to be able to guarantee good workpiece quality and at the same time to be able to produce economically. One way to meet these challenges is to carry out the forming processes in closed-loop control systems using softsensors. Despite the many potential applications of softsensors in the field of forming technology, there is still no definition of the term softsensor. This publication therefore proposes a definition of the softsensor based on the definition of a sensor and the distinction from the observer, which on the one hand is intended to stimulate scientific discourse and on the other hand is also intended to form the basis for further scientific work. Based on this definition, a wide variety of highly topical application examples of various softsensors in the field of forming technology are given.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Zwischen Überwältigung und Beliebigkeit - Wertorientierung im Unterricht als Aufgabe der Lehrpersonenbildung - Schlegel-Matthies, Kirsten (Nachdenken über Lehrerinnen- und Lehrerbildung. Anregungen zur Weiterentwicklung der Pädagogischen Hochschulen in der deutschsprachigen Schweiz. Aus Anlass des 20-Jahre-Jubiläums der Pädagogischen Hochschule Luzern)

Teacher's roles and teacher professionalism - Lin-Januszewski, Liang-Wen (Sociology of education: Theory, experience and implication)

Similar Affordances, Different Use Practices? An Investigation of Socio-Cultural Contexts in Facebook, Instagram and Twitter - Arslan, Kader; Trier, Matthias (Proceedings of the 44th International Conference on Information Systems (ICIS 2023))